Keefektifan Penggunaan Non-Nutritive Sucking untuk Mengurangi Rasa Nyeri pada Neonatus - Uray Pardinan; Yeni Rustina (FORIKES, 2021)
Pain in neonates results in disruption of physiological behavior, metabolic responses and brain development which in turn can lead to impaired intelligence and behavior in the future. One of the non-pharmacological interventions to reduce pain in neonates is the use of non-nutritive sucking (NNS). This study analyzed the effectiveness of NNS compared to other nursing interventions in reducing pain in neonates. The literature used were articles published from 2016 to 2020 from ProQuest, Scopus, ScienceDirect, Wiley, Clinical Key and Taylor & Francis. The results of the review show that the use of NNS is very effective for reducing neonatal pain during invasive procedures or heel punctures. NNS is recommended to be carried out in conjunction with other interventions such as giving sucrose, lullaby (Brahma), and the smell of breast milk, in order to provide comfort to the neonate. Keywords: neonates; non-nutritive sucking (NNS); pain ABSTRAK Nyeri pada neonatus mengakibatkan terganggunya perilaku fisiologis, respon metabolik dan perkembangan otak yang selanjutnya dapat menimbulkan gangguan kecerdasan dan perilaku di masa depan. Salah satu intervensi non farmakologis untuk mengurangi nyeri pada neonatus adalah penggunan non-nutritive sucking (NNS). Studi ini menganalisis efektivitas NNS dibandingkan dengan intervensi keperawatan lainnya dalam rangka mengurangi nyeri pada neonatus. Literatur yang digunakan adalah artikel terbitan tahun 2016 sampai 2020 dari ProQuest, Scopus, ScienceDirect, Wiley, Clinical Key dan Taylor & Francis. Hasil review menunjukkan bahwa penggunaan NNS sangat efektif untuk mengurangi nyeri neonatus pada saat tindakan invasif atau penusukan tumit. NNS direkomendasikan dilakukan bersamaan dengan intervensi lainnya seperti pemberian sukrosa, lagu pengantar tidur (Brahma), dan bau ASI, dalam rangka memberikan kenyamanan pada neonatus. Kata kunci: neonatus; non-nutritive sucking (NNS); nyeri